2018
DOI: 10.1186/s40623-018-0793-9
|View full text |Cite
|
Sign up to set email alerts
|

Using Himawari-8, estimation of SO2 cloud altitude at Aso volcano eruption, on October 8, 2016

Abstract: It is vital to detect volcanic plumes as soon as possible for volcanic hazard mitigation such as aviation safety and the life of residents. Himawari-8, the Japan Meteorological Agency's (JMA's) geostationary meteorological satellite, has high spatial resolution and sixteen observation bands including the 8.6 μm band to detect sulfur dioxide (SO 2 ). Therefore, Ash RGB composite images (RED: brightness temperature (BT) difference between 12.4 and 10.4 μm, GREEN: BT difference between 10.4 and 8.6 μm, BLUE: 10.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…This result implies that the radar echo top altitude by JMA may be overestimated. In addition, the median value is lower than 13-14 km ASL, the top altitude of SO 2 cloud estimated by Himawari-8 Ash RGB and the JMA Global Atmospheric Transport Model by Ishii et al (2018). However, the result of our method is almost equal to 39,000 feet (11.9 km) ASL, which was derived by Himawari-8 infrared bands (Tokyo VAAC 2016).…”
Section: Discussionmentioning
confidence: 58%
“…This result implies that the radar echo top altitude by JMA may be overestimated. In addition, the median value is lower than 13-14 km ASL, the top altitude of SO 2 cloud estimated by Himawari-8 Ash RGB and the JMA Global Atmospheric Transport Model by Ishii et al (2018). However, the result of our method is almost equal to 39,000 feet (11.9 km) ASL, which was derived by Himawari-8 infrared bands (Tokyo VAAC 2016).…”
Section: Discussionmentioning
confidence: 58%
“…An example is reported in Figure 7a, displaying the ash RGB product of 25 November at 22:00 UTC (see the RST ASH map of the same day and hour reported in ). The figure shows that volcanic ash, which should appear in pinkish color (see [25,27]), was difficult to be distinguished from the background (see region magnified at the top right side of the image). As can be seen from Figure 7b, modifying the Red component, i.e., analyzing the BT 11.2 − BT 10.4 spectral difference in place of BT 12.4 − BT 10.4 , the ash plume was more recognizable but at the expense of an increase of misleading features, which were mostly associated to meteorological clouds (e.g., see pink areas outside the region marked in black).…”
Section: Discussionmentioning
confidence: 99%
“…The improved features of the AHI instrument, in terms of spectral, spatial and temporal resolution, should guarantee a more efficient monitoring of rapidly changing weather/environmental phenomena in comparison with imagers of the previous MTSAT series [18]. In particular, the AHI infrared bands 7 (3.74-3.96 µ m), 11 (8.44-8. Although a number of studies up to now have been performed exploiting Himawari-8 observations (e.g., [21][22][23][24]), only a few of them focused on volcanic ash (e.g., [25,26]). Some authors In this work, we investigate the ash events of 25-28 November 2017 from space by implementing the well-established RST ASH algorithm [14][15][16], which was previously tested over the Asiatic region using infrared MTSAT-1R/2 (Multi-Functional Transport Satellite-1R/2) observations [17], for the first time on Himawari-8 data.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that these techniques can be effective to monitor the degassing activity of the volcanoes. Ishii et al (2018) used the Ash RGB images from Himawari-8 to detect and track SO 2 cloud from a phreatomagmatic eruption of Aso volcano on October 8, 2016. The Ash RGB is a composite image of three observation bands of Himawari-8 (RED: brightness temperature difference between 12.4 and 10.4 μm, GREEN: brightness temperature difference between 10.4 and 8.6 μm, and BLUE: 10.4 μm), and can discriminate SO 2 clouds and volcanic ash clouds from meteorological clouds.…”
Section: Remote Sensingmentioning
confidence: 99%